Inpatients Hospital Care for Older People - R Fadayevatan; SG Parker; T Warnes (Tehran University of Medical Sciences, 2005)
Comprehensive geriatric assessment (CGA) has become associated with a set of approaches to service provision in the care of older people. The models can be used in a variety of settings, including hospital inpatients, ambulatory care and nursing home care. In CGA programmes the multidisciplinary, multidimensional nature of the assessment of health, rehabilitation and social care needs is formalised, often using standardised assessment instruments. The results of these formal assessments are then either used to inform or prompt treatment and management recommendations which may be carried out in dedicated inpatient units (Geriatric Evaluation and Management Units- GEMU), provided as recommendations to the referring physician or team (Geriatric Consultation Service), or delivered in the patient's home or other ambulatory care setting such as the day hospital or outpatient clinic. During the past 5 years or so, a key issue in the delivery of comprehensive assessment processes is the notion that they should be targeted to frail older people. In this context, frailty is now a well-defined and measurable concept, which has been shown to associate with key clinical syndromes in disease presentation. Measures of frailty can therefore be used to identify "need" for multidimensional assessment. Further, measures of frailty have been shown in some populations to be more effective predictors of outcome (principally mortality) than conventional clinical measures (such as diagnosis, specific disease severity or age). Being able to relate measures of frailty and comprehensive assessment to outcomes in the UK will help us to develop and target appropriate health care technologies more effectively and efficiently to the benefit of older people in need of inpatient hospital care. So; this study is to examine Interaction between CGA, Frailty and Clinical Syndrome and their Effects on Outcomes in Elderly hospitalized patients in Barnsley Hospital. Sheffield, UK.